CONCEPTUAL APPROACHES TO THE CREATION OF UNIVERSITY ELECTRONIC LIBRARIES - P. M. Lapo (Informatika, 2016)
The peculiarities of informatization in education, conceptual approaches to the creation of electronic libraries, as well as the content and the rating of the electronic library of Belarusian State University are considered.